2020
DOI: 10.1080/17453674.2020.1803664
|View full text |Cite
|
Sign up to set email alerts
|

Automated classification of hip fractures using deep convolutional neural networks with orthopedic surgeon-level accuracy: ensemble decision-making with antero-posterior and lateral radiographs

Abstract: Background and purpose — Deep-learning approaches based on convolutional neural networks (CNNs) are gaining interest in the medical imaging field. We evaluated the diagnostic performance of a CNN to discriminate femoral neck fractures, trochanteric fractures, and non-fracture using antero-posterior (AP) and lateral hip radiographs. Patients and methods — 1,703 plain hip AP radiographs and 1,220 plain hip lateral radiographs were included in the total dataset. 150 images each of the AP and lateral vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 19 publications
2
53
0
Order By: Relevance
“…( 77 ) Twelve studies compared ML model performance versus human experts. ( 66,71,78–83,85,91,93,94 ) In four of these studies, ML outperformed human experts significantly. ( 80,83,85,91 ) Thirteen studies applied transfer learning based on pre‐defined CNN architectures, pre‐trained on the ImageNet data set ( 77,79–83,85,90,91,93,95 ) or on a radiography image database.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…( 77 ) Twelve studies compared ML model performance versus human experts. ( 66,71,78–83,85,91,93,94 ) In four of these studies, ML outperformed human experts significantly. ( 80,83,85,91 ) Thirteen studies applied transfer learning based on pre‐defined CNN architectures, pre‐trained on the ImageNet data set ( 77,79–83,85,90,91,93,95 ) or on a radiography image database.…”
Section: Resultsmentioning
confidence: 99%
“…( 75,76,90–97 ) Nineteen studies developed CNN models for image analysis. ( 66,67,71,72,77–86,90,91,93–95 ) Others used features extracted from images or collected from non‐imaging data. ( 68–70,73–77,87–89,92,96,97 ) Studies reported average best AUC of 0.92 (range 0.63 to 1.00) and average best accuracy of 89.8% (range 78.4% to 99.1%].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations